Effect of Pomegranate Extract Topical Cream (Punica granatum) on SOD and TNF-α Levels in Wistar Rats Excision Wound Model - Retta Adhimarta Atmaja; Agung Putra; Titiek Sumarawati (Poltekkes Kemenkes Surabaya, 2024)
Wounds cause damage or loss of skin tissue components. The body will respond and trigger the wound healing process. Neutrophils will trigger the pro-inflammatory mediator, Tumor Necrosis Factor alpha (TNF-α) which is useful for starting inflammation. Providing exogenous antioxidants, such as those found in pomegranates, is very important. Pomegranate extract contains antioxidants such as flavonoids, alkaloids, tannins, triterpenes and saponins which have the potential to be a new treatment for inflammation caused by various skin disorders. Pomegranate extract significantly improves the wound healing process. However, an in-depth analysis of pomegranate extract cream which can accelerate the healing of excision wounds and influence SOD and TNF-α levels needs to be carried out, so that the results of this research can be a new alternative that supports topical wound treatment. An in-vivo experimental study was conducted with 48 Wistar rats, divided into 12 groups. The analysis was performed in two stages: six groups were analyzed after 3 days of treatment, and the remaining six groups were analyzed after 7 days of treatment. Data were tested using one-way ANOVA. Pomegranate extract cream reduced TNF-α levels, as shown by the One-Way ANOVA test (p=0.001, p<0.05). On day 3 after treatment, pomegranate extract cream had the same effect as the bioplacenton group. There was no significant difference between groups in SOD levels on day 3 after treatment, as indicated by the One-Way ANOVA test (p=0.565, p>0.05). However, on day 7 after treatment, there was a significant difference in SOD levels between groups, as shown by the One-Way ANOVA test (p=0.037, p<0.05). Pomegranate extract cream reduces TNF-α levels to the same extent as bioplacenton on day 3 after treatment and increases SOD levels in excision wounds on day 7 after treatment.